Business Model Canvas and SWOT Analysis as a Development Strategy Frozen Food Culinary Industry - Basuki, Carola (Journal of Business, Management, and Social Studies, 2023)
The purpose of this study is to analyze the business condition of the home industry Frozen Food Pempek Palembang Kukuinutri using Business Model Canvas. Next, to create a new Business Model Canvas Frozen Food Pempek Palembang Kukuinutri, the scope of this research is focused on analyzing Business Model Canvas along with internal (importance and performance) and external (industry competition) factors of home industry Frozen Food Pempek Palembang Kukuinutri, as well as the formation of new business models using BMC based on future industries. The research method used is descriptive with a qualitative approach. Data collection was carried out using interview techniques with the owner of Frozen Food Pempek Palembang Kukuinutri. This type of research is a case study. The analysis technique used is SWOT analysis to see the weaknesses and threats faced by optimizing the advantages and opportunities owned and business mapping using the Business Model Canvas (BMC). This research produces solutions that can be used by business owners to be able to expand market reach on the Value Proposition element by attending business development training so that the products produced are more varied, Channel elements to add channels by participating in Bazar Events, Key Resources elements by creating production houses and more competent workforce, Key Partner elements to make halal logo certification and BPOM. The results of this research will later be used to create strategies to increase revenue streams, especially for planning offline store openings.